2014
DOI: 10.1080/14703297.2014.995202
|View full text |Cite
|
Sign up to set email alerts
|

Enabling microblogging-based peer feedback in face-to-face classrooms

Abstract: The purpose of this paper is to understand student interaction and learning in microblogging-based peer feedback sessions. The researcher examined through a case study how students interacted and provided peer feedback for each other when Twitter was enabled as a backchannel; students were also asked to report how they perceived their experience. The findings suggested that students participated actively in the microblogging-based peer feedback sessions. Although Twitter supported cognitive and corrective feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…One possible reason is that students are apt to digress from the learning topic when social networking tools and cell phones are easy to reach in face-to-face environments. This finding echoes with prior researchers noting the possibilities of creating distraction being one common drawback of using social networking tools like Twitter ; P. C. Luo, 2016;.…”
Section: Number Of Tweetssupporting
confidence: 82%
See 1 more Smart Citation
“…One possible reason is that students are apt to digress from the learning topic when social networking tools and cell phones are easy to reach in face-to-face environments. This finding echoes with prior researchers noting the possibilities of creating distraction being one common drawback of using social networking tools like Twitter ; P. C. Luo, 2016;.…”
Section: Number Of Tweetssupporting
confidence: 82%
“…Microblogging is a type of lightweight online application that allows a burst of multimedia content to be published and shared with others worldwide on the web (Java, Song, Finin, & Tseng, 2007). Research has reported its benefits and potential in allowing instant feedback and comments alongside the main channel of instruction or information (Kimmons & Veletsianos, 2016;Li & Greenhow, 2015;Luo, 2015Luo, , 2016, promoting interaction and engagement (Domizi, 2013;Luo, Smith, & Cheng, 2016;Munoz, Pellegrini-Lafont, & Cramer, 2014), and boosting academic achievement (Junco, Elavsky, & Heiberger, 2013;Kassens-Noor, 2012;Van Vooren & Bess, 2013). Nevertheless, studies that specifically address the process of knowledge construction in the context of microblogging tools have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…This mode of learning goes beyond the traditional classroom environment (Evans, 2014). Twitter has been empirically used as a pedagogical tool across different disciplines and settings (Dunlap & Lowenthal, 2009;Krutka et al, 2017;Luo, 2015Luo, , 2016Selwyn & Stirling, 2016). Researchers in the past have reported that microblogging could be used to share resources instantly with the learners.…”
Section: Pedagogical Use Of Twittermentioning
confidence: 99%
“…Likewise, micro-blogging platforms (e.g., Twitter) are used to stimulate student engagement in the classroom. In particular, Twitter enables students to share their thoughts about a discussion topic within 140 characters [13,31,32,47].…”
mentioning
confidence: 99%